2015
DOI: 10.1007/s00018-015-1904-4
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular and cellular mechanisms that initiate pain and itch

Abstract: Somatosensory neurons mediate our sense of touch. They are critically involved in transducing pain and itch sensations under physiological and pathological conditions, along with other skin resident cells. Tissue damage and inflammation can produce a localized or systemic sensitization of our senses of pain and itch, which can facilitate our detection of threats in the environment. Although acute pain and itch protect us from further damage, persistent pain and itch are debilitating. Recent exciting discoverie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
80
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 303 publications
(355 reference statements)
0
80
0
3
Order By: Relevance
“…Eact elicits both itch-and pain-related behaviours in a TRPV1-dependent manner TMEM16A is activated by increased intracellular free Ca 2+ ([Ca 2+ ] i ) evoked by activation of many GPCRs including the histamine H 1 receptor and endothelin ETA receptor, which are important itch mediators (Cho et al, 2012;Luo et al, 2015;Yang et al, 2008). Furthermore, TMEM16A is also reported to mediate the bradykinin-induced nocifensive response and is required for generating nociceptive behaviours in mouse models of thermal pain (Jin et al, 2013;Liu et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Eact elicits both itch-and pain-related behaviours in a TRPV1-dependent manner TMEM16A is activated by increased intracellular free Ca 2+ ([Ca 2+ ] i ) evoked by activation of many GPCRs including the histamine H 1 receptor and endothelin ETA receptor, which are important itch mediators (Cho et al, 2012;Luo et al, 2015;Yang et al, 2008). Furthermore, TMEM16A is also reported to mediate the bradykinin-induced nocifensive response and is required for generating nociceptive behaviours in mouse models of thermal pain (Jin et al, 2013;Liu et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Median heat response thresholds did not differ between C-fibers from HbSS-BERK sickle mice (40[38,43]°C) and those from HbAA-BERK control mice (42[40,42]°C; Mann-Whitney U = 37.0, n 1 = 9, n 2 = 11, n.s.). In C-fibers exposed to the entire range of heat stimuli, those from HbSS-BERK mice exhibited higher cumulative responses (118.9±16.2 impulses vs. 65.7±18.2 impulses; t 18 = 2.1, p <.05), but responses to individual temperatures did not differ between the groups ( F 1,18 = 0.5, n.s., Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the CB2 receptor agonist JWH-133 reduced deep tissue hyperalgesia and attenuated mast cell degranulation [60]. Degranulation of mast cells releases inflammatory mediators that sensitize nociceptors (see reviews [2,3,26,40]).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that sensory transient receptor potential cation channel subfamily V member 1 (TRPV1) and subfamily A member 1 (TRPA1) channels are selectively expressed by a subpopulation of primary afferent nociceptors and serve as molecular integrators for numerous endogenous pruritogens released by skin-resident cells to provoke both histaminergic and non-histaminergic itch 7 . Furthermore, the TRPV1-expressing sensory fibers mediate skin inflammation through facilitating the function of dermal immune cells in a mouse model of psoriasis 8 .…”
Section: To the Editormentioning
confidence: 99%